The microbiological safety of food in healthcare settings (Blackwell Pub., 2008)
Drawing together the work of a wide range of experts, this extremely important book provides a clear, practical account of the salient features of foodborne pathogenic microorganisms and of the particular risks that they pose to vulnerable groups of the population in hospitals, nursing and residential homes, nurseries, and in the community at large.